MANAJEMEN PRODUKSI PROGRAM BERITA TANAH DATAR TV DI DINAS KOMUIKASI DAN INFORMATIKA KABUPATEN TANAH DATAR - Putri, Windya; Fadilla, Siti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The development of information and communication technology has changed the way information is conveyed and presented. Nowadays, information is no longer limited to printed form, but is also available in electronic form that can be accessed via the internet. This progress has resulted in the growth of news media through social media accounts, so that online news social media is now the main channel for conveying news and information. The main problem in this thesis is how to manage the production of news programs for online media. The purpose of this research is to determine the process of planning, organizing, implementing and supervising the Tanah Datar TV team in publishing news to produce quality journalistic products for readers. The type of research used is qualitative research with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction (summarizing, selecting the main things, focusing on important things, looking for themes and patterns), data presentation (brief description/relationship between categories/flowchart/and the like), and drawing conclusions. The techniques used to ensure the validity of the data are source triangulation, technical triangulation and time triangulation. The results of this research concluded that the Tanah Datar TV team's planning process was a daily projection meeting. Organizing the Tanah Datar TV team, namely through recruitment and basic training. Actuating (implementation) of the Tanah Datar TV team by collecting projected news and paying attention to writing accuracy, accuracy of sources and balance of content. Controlling (supervision) of the Tanah Datar TV team is carried out with layered actions, namely editing by the editor with attention to substance, review by the managing editor taking into account the impact of the content, and accountability by the editor-in-chief taking into account media cooperation.